Perbedaan Career Decision Making Self-Efficacy Ditinjau dari Keikutsertaan MBKM - Ayu Wandari Situmorang; Hotpascaman Simbolon (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This program is a new breakthrough formed by the Ministry of Education, Culture, Research and Technology to improve human resources with high status and morals. Merdeka Campus as one of the programs realized by the ministry of education under the leadership of Nadiem Makarim as Minister of Education. In the Merdeka Learning Campus program, students have the freedom to study in a college or outside a college, which is a new concept in realizing an independent campus. As stated in the law on National Standards for higher education based on Permendikbud 3 of 2020 concerning National Standards for higher education is a general basis that covers National Education Standards, along with Research Standards and Community Service Standards.Research Sample The sample in this study are active students in Indonesia who have or are currently participating in the fourth MBKM Teaching Campus program of 388,042 people, 394,356 MBKM Certified Internships and 392,885 third MBKM Independent Studies taken using Purposive Sampling technique. Based on the results of the trial, the reliability coefficient (α) for the CDMSE scale was 0.944 was canceled because it had a total item correlation value of less than 0.5. This researcher groups CDMSE variables using high, medium and low categorization. In the statistical test results above, it can be seen that the subjects who participated in the Teaching Campus had a significance value of 0.063, Independent Study had a significance value of 0.00 and Certified Internship (MSIB) had a significance value, namely 0.055, so it can be interpreted that the distribution of Teaching Campus and Certified Internship data in this study is said to be normally distributed. Meanwhile, the distribution of Independent Study data in this study is not normally distributed.In the statistical test results above, the significance value in the subjects who attended the Teaching Campus, Independent Study and Certified Internship (MSIB) was obtained as 0.066, it can be interpreted that the data distribution was homogeneous. Keywords: Career Decision Making Self-Efficacy, MBKM